PERSPEKTIF PERUSAHAAN: MENILAI FINANCIAL SUSTAINABILITY MELALUI ANALISIS RASIO LIKUIDITAS, PROFITABILITAS, DAN AKTIVITAS - Ramadhani, Alia Pramudita; Sari, Shinta Permata (ITB AAS Indonesia Surakarta, 2024)
Financial sustainability is the company’ ability to maintain financial performance and business sustainability in the long term. Financial Sustainability is also important for companies to predict the potential going concern for its future. This study aims to analyze financial sustainability from the company’s perspective through analysis of liquidity, profitability, and activity ratios in consumer non cyclicals sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sampling technique used is a purposive sampling technique with the number of samples are 101 data over the 2021-2023 period. The research method used is quantitative method with multiple linear regression analysis as a data analysis technique. The result of this study suggest that liquidity and profitability ratios affect financial sustainability, while activity ratios do not affect financial sustainability. Keywords : financial sustainability, liquidity, profitability, activity.